EWSR1-PATZ1-rearranged sarcoma with rhabdomyoblastic differentiation- Case report and review of the literature - Laura M. Warmke; Jeanne M. Meis (Elsevier, 2021)
Round cell sarcomas with EWSR1-non-ETS fusions are a rare group of sarcomas, entirely distinct from Ewing sarcoma with canonical fusion, of which EWSR1-PATZ1-rearranged sarcomas are emerging as a distinct entity. Only a few cases of this sarcoma have been reported in the literature, and none have previously described a case with overt rhabdomyoblastic differentiation, representing an important potential diagnostic pitfall. Herein we report the histologic features, immunohistochemical characteristics, clinical course, and differential diagnosis for the first known case of EWSR1-PATZ1-rearranged sarcoma with overt rhabdomyoblastic differentiation arising in the abdominal wall of a 40-year-old patient. We also review other published cases to evaluate distinguishing characteristics of this rare sarcoma. Given the possible aggressive nature of this tumor, knowledge of this rare entity with recognition of rhabdomyoblastic differentiation within its histologic spectrum is essential to ensure proper management and prevent misdiagnosis.